The Effect of Probiotic Giving on Body Size Broiler Chicken Aged 2-4 Weeks - Rusli Badaruddin; La Ode Nafiu; Muhammad Amrullah Pagala; La Ode Muh Munadi (Budapest International Research and Critics University, 2022)
The study aimed to determine the effect of giving different probiotics to the growth rate of several body parts of broiler chickens such as chest circumference, femur length, tibia length, and body length at 2-4 weeks of age with 100 MB 202 platinum strain using BP 11 commercial feed, probiotic supplements. Liquid organics, Lacto probiotics, and local probiotics (tape yeast). The research method used a completely randomized design (CRD) then the data obtained were analyzed employing variance (ANOVA) and if there was a significant effect, it was continued with the Duncan Multiple Range Test (DMRT). The results of the analysis showed that the administration of tape yeast in broiler drinking water showed a significant effect (p<0.05) on the increase in chest circumference, femur length, and body length which was greater than liquid organic probiotics and lacto.